Challenges In Preparing Human Resources with Global Competence: A Case Study on The Dayak Community in Kalimantan Barat - Sada, Clarry (an1mage, 2019)
This paper will focus on the Dayak tribe. In recent time, the participation of the Dayak in all aspects of life has existed though the participation is not significantly happen. In the aspect of politics, there are some Dayak’s politicians who are seated as the member of parliament or house of representatives. They have taken part actively in building and developing this nation though it is still under their expectation. The number of Dayak’s politicians to re[present their group might be not significantly with the Dayak’s population, therefore, their struggle to support their community might be not so strong.